Pengaruh Konsentrasi Perekat Molase Terhadap Kualitas Briket Sekam Padi - Moh Akbar Suryo Prasetyo (Nozel : Jurnal Pendididikan Teknik Mesin, 2026)
This study aims to determine the effect of molasses adhesive concentrations on the quality of rice husk briquettes then to formulate optimal composition projections to approach national quality standards. This study employed an experimental method with a descriptive analysis design, in which briquette fabrication data at laboratory. The material processing technique for rice husk charcoal used a 50 mesh sieve, while the adhesive variations used progressive concentrations. Data collection techniques were conducted through temperature measurements and duration observations. The results showed that the 5 wt  molasses concentration aspect achieved a heating value of 4,645 cal/g categorized as "below standard", the 10 wt  molasses concentration aspect achieved 5,183 cal/g, and the 15 wt  molasses concentration aspect achieved 6,411 cal/g. Overall, the quality of the rice husk briquettes toward Class A (penjelasan) standards reached an optimal value categorized as "very appropriate". The briquette development projection is directed toward increasing the adhesive concentration, maintaining a constant density, and stabilizing the combustion rate in accordance with national standards.